Proteomic profiling of arteriovenous fistula tissue identifies dysregulated oxidoreductase proteins in diabetic end-stage renal disease - Zhao, Bin; Zhan, Shen; Zhou, Xue; Yu, Pei; Wang, Yuzhu (Frontiers in Endocrinology, 2026)
BackgroundDiabetes mellitus is a leading cause of end-stage renal disease (ESRD), with up to 35% of patients with diabetes mellitus developing kidney disease. This study aims to monitor protein expression changes in ESRD patients with and without type 2 diabetes mellitus (T2DM).MethodsA total of 186 ESRD patients who underwent arteriovenous fistula creation surgery were enrolled in this study. Of these, 148 patients were classified into the T2DM (n = 73) and non-T2DM (n = 75) groups. Data-independent acquisition proteomic analysis was conducted to analyze differentially expressed proteins. Enzyme-linked immunosorbent assay kits, immunohistochemical staining, Western blotting were employed to validate the differently expressed proteins within the cohort.ResultsProteomic analysis identified 26 upregulated and 15 downregulated proteins in the T2DM group compared with the non-T2DM group. The serum concentrations of 4-hydroxynonenal, malondialdehyde, and glutathione were elevated in the T2DM group. The immunohistochemical staining index for GPX4 and xCT was lower, while α-SMA, IL-6, TNF-α, and TGF-β levels were higher in the T2DM group compared with the non-T2DM group. Western blotting indicated the downregulation of SOD1 and GPX4 as well as upregulation of PTGS2 and ACLS4 in the T2DM group accompanied by increased levels of Fe2+, total iron, and Fe3+.ConclusionThis study underscores oxidoreductase activity-related proteins, including ferroptosis-related proteins to be differentially expressed in ESRD combined with T2DM.